A Modern Solution to the Gion Shrine Problem. Issue 2 (15th March 2019) - Arias de Reyna, J.; Clark, David; Elkies, Noam D.
Summary: We give a new solution to the famous Gion shrine geometry problem from eighteenth-century Japan. Like the classical Japanese solution, ours is given in the form of a degree-ten equation. However, our polynomial has the advantage of being much easier to write down. We also provide some additional analysis, including a discussion of existence and uniqueness. Finally, we prove that the Gion shrine problem has no rational solutions.